A Proposed Saffron Soilless Cultivation System for a Quality Spice as Certified by Genetic Traceability - Alessandro Mariani; Gianpiero Marconi; Nicoletta Ferradini; Marika Bocchini; Silvia Lorenzetti; Massimo Chiorri; Luigi Russi; Emidio Albertini (Plants)
Saffron (Crocus sativus L.) is one of the most expensive spices in the world due to its strong market demand combined with its labor-intensive production process, which needs a lot of labor and has significant costs. New cultivation methods and traceability systems are required to improve and valorize local Italian saffron production. In this study, we conducted a three-year trial in Umbria (Central Italy), looking for a soilless cultivation method based on wooden bins posted at a suitable height from the ground to ease the sowing of corms and harvesting of flowers. Moreover, the spice traceability could be based on investigating the genetic variability of Italian saffron populations using SNP markers. The proposed novel cultivation method showed significantly higher stigma and corm production than the traditional one. At the same time, the genetic analysis revealed a total of 55 thousand SNPs, 53 of which were specific to the Italian saffron populations suitable to start a food traceability and spice certification.